Retrospective analysis of outcomes of secondary debulking surgery for recurrent epithelial ovarian cancer with favorable prognostic factors. Issue 3 (18th November 2013) - Nasu, Kaei; Kai, Kentaro; Hirakawa, Tomoko; Nishida, Masakazu; Matsumoto, Harunobu; Kawano, Yasushi; Narahara, Hisashi
Abstract Aim Ovarian cancer is the second most common gynecological malignancy, yet it has the highest case‐fatality ratio of all gynecologic malignancies. Surgery followed by combination platinum‐taxane chemotherapy is the standard approach to the management of primary epithelial ovarian cancer. However, standard treatment of patients with recurrent ovarian cancer remains poorly defined. Secondary cytoreductive surgery (SDS) at the time of relapse has been proposed as a means of improving the prognosis of recurrent ovarian cancer patients with a treatment‐free interval of at least 6 months. Methods In the present study, we retrospectively collected 16 patients with recurrent epithelial ovarian cancer who might benefit most from SDS and evaluated the impact of SDS on the outcomes for this highly select patient group. Results We found that SDS led to excellent outcomes, with a 73.1% 8‐year overall survival rate after initial treatment, a 67.9% 5‐year overall survival rate after prior SDS, and a 31.3% 5‐year progression‐free survival rate after prior SDS. Although the findings were not significant, these results suggest that repeated SDS might improve outcomes for this patient group. Conclusion The present study may provide a platform for discussion of the impact of aggressive or repeated SDS on the survival of patients with recurrent epithelial ovarian cancer and favorable prognostic factors. Further multi‐institutional studies with larger number of patients are mandatory to confirm the present findings.